Iridium-coated ruthenium nanocatalysts for optimization of oxygen evolution reaction in acidic and alkaline media - Seow, Justin Zhu Yeow (2018)
Currently, as the threat of global warming intensifies, exploration of ways to efficiently and economically use renewable sources of energy is becoming more essential. Varying power supply by solar and wind energies as well as the need for a carbon-free fuel in fossil fuel-dominant transportation sector have increased demand for energy storage. Hydrogen, currently being one of the best choice for energy storage, is mostly produced from natural gas. To increase the role of water electrolysis in producing hydrogen, its efficiency, limited by oxygen evolution reaction (OER), has to increase. Based on various successful core-shell structuring strategy for OER nanocatalysts, an Ir-coated Ru core-shell-like nanoparticle with Ru-to-Ir atomic ratios of 3:7, 3:10 and 3:15 (Ru3@Ir7, Ru3@Ir10 and Ru3@Ir15 respectively) were synthesized. At overpotential of 200 mV (1.43 V versus RHE), Ru3@Ir10 nanocatalyst recorded the highest specific OER activities (0.61 μA/cm2oxide in KOH and 8.02 μA/cm2oxide in HClO4) and highest mass activities (0.53 A/goxide in KOH and 6.92 A/goxide HClO4) among the bimetallic nanocatalysts in this study, with higher stability and lower dissolution compared to Ru nanocatalyst after 50-cycle cyclic voltammetry protocol in both electrolytes. The substantially stable and highly catalytically active (near) core-shell nanocatalyst has high potential for usage in water electrolysers in both acidic and alkaline media.